Producing Digital Biological Generations: Integrating Cinematography Techniques in Problem-Based Biological Environment Investigation Learning Models - Wibowo, Agung; Sulistiarini, Dwi; Balqis, Balqis (BIOEDUSCIENCE, 2024)
Background: The need for education cannot be separated from technology as a crucial basic literacy skill essential for solving problems that occur in the surrounding environment. The purpose of this research is to determine the effectiveness of the Problem-Based Biological Environment Investigation model with Cinematographic Techniques in improving the digital literacy skills of high school students. Methods: The research method used is Classroom Action Research conducted in two cycles. The research subjects are 34 students from class X-A at SMAN 3 Malang. The success indicators of the research are the implementation of the Problem-Based Biological Environment Investigation model with Cinematographic Techniques according to the referenced syntax and the increase in the percentage of students' digital literacy skills. The research instruments include observation sheets for the feasibility of the learning process and observation sheets for the digital literacy skills of the students. Results: Based on the observation results, the implementation of the Problem-Based Biological Environment Investigation model with Cinematographic Techniques according to the referenced syntax includes problem orientation, organizing students, investigative activities, presenting results, and reflective evaluation. This learning model is also effective in improving students' digital literacy skills by 33.85%. especially in the indicator "Uses to Produce Original Works.” Conclusions: Based on the findings of the research, it can be concluded that the implementation of the Problem-Based Biological Environment Investigation model with Cinematographic Techniques is effectively able to enhance the digital literacy skills of high school students.